Oral Peer Feedback in A Flipped Speaking Job Interview Class: Practice And Learners’ Attitudes - Sumardi; Khairani Dian Anisa; Lailatun Nurul Aniq (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2020)
Since flipped learning facilitates student-centered approach, it is necessary to administer such assessment which involves students’ participation. As the assessment as learning, peer feedback facilitates students to offer and receive comments from their peers. The present study aimed at investigating the practice and students’ voices of peer feedback in their flipped speaking job interview class. Twelfth graders of a state vocational high school in Indonesia (n=30) participated in this case study. The data gathered from the result of observation, student questionnaire, and semi-structured interview. The study indicated that students had a positive attitude toward peer feedback. It fostered more interaction with peers resulting in a more dynamic atmosphere. Moreover, students perceived peer feedback as a useful activity to locate their errors and learn strategies to soften their comments. The study serves as a guideline for applying peer feedback in the speaking area utilizing flipped instruction.